PERANCANGAN DESAIN PRODUK DENGAN KONSEP SILANG BUDAYA: Studi Kasus Perancangan Tas Dengan Konsep Silang Budaya Cina Peranakan dan Kontemporer - Devanny Gumulya; Merdy Batangtaris; Nathalisa Octavia (Jurnal Dimensi Seni Rupa dan Desain, 2013)
Abtract Local culture applied to product design great potential for value enhancement and global market recognition, this known as cross cultural design. The purpose of this paper is to explore the meaning of cultural objects from cultures and to extract their cultural values into design elements. The particular cultural object chosen for this study was fashion objects of China cross breed with study focuses on analyzing the apperance , how they are used and their cultural symbolic meaning. Finally , this paper establishes a study case to provide product designers with a valuable reference for designing a succesful cross cultural product. The results presented herein are framework for designer to use cultural objects as inspiration in the design process Abstrak Seni budaya lokal diaplikasikan pada desain produk semakin digemari di pasar global, hal ini berisi penjabaran metode bagaimana proses transformasi nilai dan makna dari objek budaya menjadi elemen desain. Busana Cina Perankan diambil sebagai contoh objek budaya dengan kajian fokus pada tampilan, kegunaan dan makna simbolik budaya dan aplikasinya dalam proses perancangan deain produk. Hasil akhir yang dalam mendesain produk berkonsep silang budaya yang baik.